Ictiofauna de um sistema de lagos formados com a criação de um reservatório e sua importância para a diversidade local - Boratto, Igor Alves (2015)
Dam construction and reservoir formation are important impacts that influence ecological integrity of floodplains by altering natural river flow. Reservoirs are heterogeneous environments and show a longitudinal gradient of environmental conditions. Dams create marginal flooded environments with lakes presenting different levels of connection with the reservoir when dams are built downstream from natural floodplains. Marginal lakes presente seasonal variations due to reservoir level. Our goal was to understand the role of new flooded environments created with Funil reservoir for the maintenance of fish assemblages. And also understand the influence of seasonality on community structure comparing different systems: reservoir itself, natural marginal lakes and lakes formed by the reservoir (isolated or permanently connected). Fishes were sampled using gillnets from August 2013 until June 2014 in four natural marginal lakes of Mortes’ river and eight reservoir lakes: three isolated and five permanently connected. Four localities were also sampled in the reservoir between the lakes. Differences in fish composition were tested using a Nonmetric Multidimensional Scaling (NMDS) analysis followed by an analysis of similarity(ANOSIM). A SIMPER analysis was used to verify which species contributed for dissimilarities between systems. Βeta diversity for each environment was calculated by: β = γ-α. The influence of seasonality on assemblages was investigated comparing the richness, CPUEb and CPUEn of each system throughout the year. The effect of seasonality on assemblage structure was tested through an analysis of similarity followed by a SIMPER analysis to identify the main species responsible for dissimilarities throughout the year. A total of 2023 fishes were sampled accounting for 16 families and 27 species. Connected lakes had 19 fish species, while isolated lakes and the reservoir had 17 and 20 fish species, respectively. Differences between connected lakes and the reservoir and between marginal lakes and the reservoir were indicated by the analysis of similarity. Marginal lakes had the largest beta diversity despite having the smallest alpha diversity. The increase in rainfall increased the richness and the CPUEn at the end of the season and also increased the dissimilarity between environments. These results indicate that such environments can support fish populations different from those present in the reservoir and more similar to those of natural marginal lakes. Seasonality promoted an increase in species richness especially in connected laakes. These environment may be playing an important role in the local conservation of some fish species affected by the dam.